THE DIALECTICS OF DIALECTICS: HOW SOCRATES SURVIVED (IN) STELLENBOSCH - Painter, Desmond (PINS-Psychology in Society, 2025)
Nash, Andrew (2009) The dialectical tradition in South Africa. New York & London: Routledge. ISBN 978-0415-97530-8 hbk. Pages xv + 247. I can quite easily imagine – fuelled by a certain longing, no doubt – an alternative intellectual universe, proudly South African nonetheless, in which this remarkable book by Andrew Nash would have been eagerly anticipated; in which its publication would have been met by broad discussion and debate, by refinement and refutation; and in which its legacy would have included the bestowal of renewed currency, a kind of intellectual afterlife, to almost-forgotten scholars, traditions, problematics, and books …